Evaluation of the chemical composition, protein quality and digestibility of lupin (Lupinus albus and Lupinus angustifolius) - Márcia Regina Pereira Monteiro; Aline Bárbara Pereira Costa; Suellen Fabiane Campos; Mauro Ramalho Silva; Cassiano Oliveira da Silva; Hércia Stampini Duarte Martino; Marialice Pinto Coelho Silvestre (O Mundo da Saúde)
The purpose of this study was to determine the protein quality of lupin (Lupinus albus and Lupinus angustifolius) and to determine their chemical composition, including dietary fiber. The food transformation index, protein efficiency ratio and net protein ratio were significantly higher for the casein group than for the lupin groups. The in vivo digestibility value of casein was 95.81 ± 1.60, and the DV of L. albus and L. angustifolius were 90.89 ± 2.85 and 89.30 ± 2.01, respectively. Amino acid composition scores lower than one were found for almost all essential amino acids in lupin groups. The protein digestibility corrected amino acid scores ranged from 40.00% to 89.07% for L. albus and from 30.36% to 83.05% for L. angustifolius. It was concluded that the two varieties of lupins studied are good protein sources, with no statistical difference between them, and also that this protein has an excellent digestibility, besides being a good source of dietary fiber, especially Lupinus angustifolius. Therefore, the two varieties of lupine were considered as having good quality protein and as being a good alternative for human consumption.